Doroczne Spotkanie Kanadyjskiego Towarzystwa Badań Patrystycznych (Toronto, Kanada, 29-31.05.2023) - Wysocki, Marcin (Vox Patrum, 2023)
Report from the Annual Meeting of the Canadian Society of Patristic Studies that took place on May 29-31, 2023 in Toronto, Canada.